Psychometric evaluation of the Chinese version of the Scale of Effects of Social Media on Eating Behaviour and research of its influencing factors - Kaiyan Xu; Chunguang Liang; Ying Zhao; Fan Zhang; Chunyan Zhang; Yanhong Zhang; Yefan Zhang; Zhaoquan Jiang (BMC, 2024)
Abstract Background Social media has become an indispensable part of contemporary young people's lives, and the influence of social media on college students' eating and other health-related behaviors has become increasingly prominent. However, there is no assessment tool to determine the effects of social media on Chinese college students' eating behavior. This study aims to translate the Scale of Effects of Social Media on Eating Behaviour (SESMEB) into Chinese. Its applicability to Chinese college students was examined through reliability and validity indexes, and the influencing factors of SESMEB were explored. Methods The questionnaire survey included 2374 Chinese college students. The Brislin translation model was used to translate the original scale into Chinese. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to test the construct validity of the scale, and the content validity of the scale was assessed through the content validity index. The internal consistency of the scale was assessed by calculating Cronbach's alpha coefficient, McDonald's Omega coefficient, split-half reliability, and test-retest reliability. Multiple stepwise linear regression analysis was performed to identify potential influences on the effects of social media on eating behavior. Results EFA supported the one-factor structure, and the factor loadings of each item on this dimension were higher than 0.40. CFA showed good model fitness indexes. The content validity index of the scale was 0.94. The Cronbach's alpha coefficient and McDonald's Omega coefficient for the scale were 0.964, the split-half reliability coefficient was 0.953, and the test-retest reliability was 0.849. Gender, education, major, frequency of social media use, online sexual objectification experiences, fear of negative evaluations, and physical appearance perfectionism explained 73.8% of the variance in the effects of social media on eating behavior. Conclusions The Chinese version of the SESMEB has good psychometric properties and is a valid measurement tool for assessing the effects of social media on college students' eating behavior. Subjects who were female, highly educated, non-medical, had frequent social media use, online sexual objectification experiences, fear of negative evaluations, and physical appearance perfectionism used social media to have a higher impact on eating behavior.